Identification of Genetic Determinants Controlling Seed Yield and Its Component Traits in Sunflower (Helianthus annuus) - Vanitha, J.; Mahendran, R.; Manivannan, N.; Chandirakala, R. (Current Perspectives in Agriculture and Food Science Vol. 7, 2024)
Sunflower (Helianthus annuus L.) is grown mostly as a source of vegetable oil and proteins in the world. In the course of plant improvement, plant breeders deal with several qualitative traits nowadays. The present investigation was carried out to identify the molecular markers associated with various characters in sunflowers using recombinant inbred lines. Molecular markers in applied breeding programs facilitate the appropriate choice of parents for crosses to map or tag the gene blocks associated with economically important traits. Two sunflower inbred lines namely, TNHSF239-68-1-1-1 and 17B with significant differences for various traits namely, stripe on seed surface, seed color, hull weight and oil content were selected as female and male parents respectively to develop the F2:5 population. Linkage analysis was carried out and five linkage groups were obtained with 19 simple sequence repeats (SSR) markers. Linkage map construction, single marker analysis (SMA) and composite interval mapping analysis were carried out with SSR primers and quantitative traits. In SMA, out of 50 SSR markers, a total of 29 SSR markers were found to be significantly linked to various traits. The adjusted R2 for the regression equation varies from 3.2 to 29.8%. Two traits namely, days to flowering and seed color recorded above 20% R2 value. Hull weight recorded above 10% R2 value. In inclusive composite interval mapping (ICIM), the quantitative trait loci (QTL) analysis resulted in two QTLs namely, seed and volume weight. QTL analyses were performed through inclusive composite interval mapping (ICIM). The QTL analysis revealed each QTL for traits namely, stripes on the seed margin, stripes between the seed margin, 100-seed weight and seed yield. The LOD ranged from 1.5 to 1.9. The adjusted R2 value ranged from 10.6 (seed yield) to 65.0 (stripes between seed margin) percent. Among these QTL, QTL on stripes on the seed margin and stripes between the seed margin may be considered as potential as they recorded very high phenotypic variation accounted. As the distance between the flanking marker is more than 5 cm, fine mapping of this QTL region with more markers may be attempted to utilize these QTL in the marker-assisted back cross programme.